A Play of Bodies: How We Perceive Videogames - Keogh (MIT Press, 2018)
Monograph
fulltext
Keywords: Communication, Networking and Broadcast Technologies; Components, Circuits, Devices and Systems; Computing and Processing; General Topics for Engineers